Estimation of genetic parameters of pig reproductive traits - Yang, Yiting; Gan, Mailin; Yang, Xidi; Zhu, Peng; Luo, Yi; Liu, Bin; Zhu, Kangping; Cheng, Wenqiang; Chen, Lei; Zhao, Ye; Niu, Lili; Wang, Yan; et al. (Frontiers in Veterinary Science, 2023)
Introduction: In this study, we aimed to estimate the genetic parameters of the reproductive traits in three popular commercial pig breeds: Duroc, Landrace and Yorkshire. Additionally, we evaluated the factors that influence these traits. Method: We collected data from a large number of litters, including 1,887 Duroc, 21,787 Landrace, and 74,796 Yorkshire litters. Using the ASReml-R software to analyze 11 traits, which included: total number of pigs born (TNB); number of piglets born alive (NBA); number of piglets born healthy (NBH); number of piglets born weak (NBW); number of new stillborn piglets (NS); number of old stillborn piglets (OS); number of piglets born with malformation (NBM); number of mummified piglets (NM); total litter birthweight (LBW); litter average weight (LAW); duration of gestational period (GP). We investigated the effects of 4 fixed factors on the genetic parameters of these traits. Results: Among the 11 reproductive-related traits, the gestational period belonged to the medium heritability traits (0.251-0.430), while remaining traits showed low heritability, ranging from 0.005 to 0.159. TNB, NBA, NBH, LBW had positive genetic correlation (0.737~0.981) and phenotype correlation (0.711~0.951). There was a negative genetic correlation between NBW and LAW (-0.452~-0.978) and phenotypic correlation (-0.380~-0.873). LBW was considered one of the most reasonable reproductive traits that could be used for breeding improvement. Repeatability of the three varieties was within the range of 0.000–0.097. In addition, the fixed effect selected in this study had a significant effect on Landrace and Yorkshire (P < 0.05). Discussion: we found a positive correlation between LBW and TNB, NBA, and NBH, suggesting the potential for multi-trait association breeding. Factors such as farm, farrowing year, breeding season, and parity should be taken into consideration in practical production, as they may impact the reproductive performance of breeding pigs.